2020
DOI: 10.1186/s12974-020-1721-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflammation on the kynurenine pathway in schizophrenia — a systematic review

Abstract: Background: In the last decade, there has been growing evidence that an interaction exists between inflammation and the kynurenine pathway in schizophrenia. Additionally, many authors found microglial activation in cases of schizophrenia due to inflammatory mechanisms related mostly to an increase of pro-inflammatory cytokines. In order to gain new insights into the pathophysiology of schizophrenia, it is important to incorporate the latest published evidence concerning inflammatory mechanisms and kynurenine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 94 publications
1
54
0
3
Order By: Relevance
“…However, is there a proinflammatory phenotype in SCZ? Post-mortem and clinical studies show an increase in pro-inflammatory markers in people with SCZ compared to controls (Fillman et al, 2016;Sekar et al, 2016;Boerrigter et al, 2017;Lesh et al, 2018;Goldsmith and Rapaport, 2020;Pedraz-Petrozzi et al, 2020). Moreover, there is evidence for elevated levels of cytokines in blood samples from people with SCZ, whether they are medication-naive or receiving antipsychotic treatment, during episodes of psychosis (McKernan et al, 2011;De Picker et al, 2019;Mondelli et al, 2020;Steiner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, is there a proinflammatory phenotype in SCZ? Post-mortem and clinical studies show an increase in pro-inflammatory markers in people with SCZ compared to controls (Fillman et al, 2016;Sekar et al, 2016;Boerrigter et al, 2017;Lesh et al, 2018;Goldsmith and Rapaport, 2020;Pedraz-Petrozzi et al, 2020). Moreover, there is evidence for elevated levels of cytokines in blood samples from people with SCZ, whether they are medication-naive or receiving antipsychotic treatment, during episodes of psychosis (McKernan et al, 2011;De Picker et al, 2019;Mondelli et al, 2020;Steiner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there were numerous studies suggesting that the in ammatory activation was associated with schizophrenia. The main in ammatory factors involve TNF-α, IL-6, IL-1β [14]. A meta-analysis showed that TNFα, IL-6 and IL-1β were elevated in patients with schizophrenia [14].…”
Section: Discussionmentioning
confidence: 99%
“…The main in ammatory factors involve TNF-α, IL-6, IL-1β [14]. A meta-analysis showed that TNFα, IL-6 and IL-1β were elevated in patients with schizophrenia [14]. BDNF is a neurotrophic factor that plays an important role in neuronal transport, modulation, and plasticity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Вместе с тем развитие этих патологических дименсий (позитивные/негативные расстройства) ассоциировано с двумя различными, хотя и взаимосвязанными молекулярными механизмами. В основе первого из них, определяющего развитие обратимых позитивных симптомокомплексов, лежит дисбаланс в нейротрансмиссии, формирующийся вследствие влияния провоспалительных цитокинов, синтезируемых активированной микроглией, на катаболизм триптофана и смещения его в сторону кинуренового пути [37,38]. В основе второго механизма, определяющего развитие прогрессирующих и относительно необратимых негативных изменений, лежит процесс нейродегенации, связанный с синтезом активированной микроглией большого количества нейротоксических метаболитов: активных форм кислорода, азота, глутамата, аспартата и др., что ведет к повреждению нейронов и глии, потере функционирующих синапсов и нарушению функционирования нейронных сетей [39,40].…”
Section: Informatiom About Authorsunclassified